PVWatts-Based Assessment of Solar Photovoltaic Energy Potential in Indonesian Urban Areas for Infrastructure Planning Optimization - Angga Darmawan; Kusmendar; Dimas Langga Chandra Galuh (RING ME, 2026)
The increasing demand for renewable energy in urban areas necessitates comprehensive location-based assessments of solar photovoltaic (PV) system performance. This study presents a simulation-based comparative analysis of solar energy production potential across three representative Indonesian cities: Serang (Banten Province), Yogyakarta (Special Region of Yogyakarta), and Surabaya (East Java Province), representing the western, central, and eastern geographic zones of Java Island. Using the PVWatts simulation tool with standardized system parameters and historical meteorological data, monthly and annual energy yield, solar irradiance, and AC energy output were evaluated for each location. Results indicate that Surabaya recorded the highest annual solar irradiance of 5.54 kWh/m²/day and the greatest annual AC energy production of 1,501 kWh, followed by Yogyakarta (5.27 kWh/m²/day; 1,442 kWh) and Serang (5.02 kWh/m²/day; 1,360 kWh). All three cities exhibited peak performance during the dry season (June September) and minimum production during the wet season (November February). Surabaya demonstrated the most pronounced seasonal variation, with a peak irradiance of 7.18 kWh/m²/day in September and a minimum of 3.91 kWh/m²/day in December. These findings provide a data-driven framework for optimizing solar energy infrastructure planning in Indonesian urban regions and contribute to national renewable energy transition goals aligned with Sustainable Development Goal 7.